The Influence Of Animosity, Ethnocentrism, And Religiosity On Boycott Intentions At Mcdonald's In Jabodetabek - Octavia, Margaretha; Asri, Hendri Rahmayani; Gisijanto, Hantoro Arief; Hartanti, Nenik Diah; Setyarini, Ekaning (Review: Journal of Multidisciplinary in Social Sciences, 2024)
The escalating Israeli-Palestinian conflict has sparked a global wave of solidarity, including in Indonesia. Boycotts against American products, such as McDonald’s, have become a popular form of protest. The purpose of this study is to analyze animosity, ethnocentrism, and religiosity on boycott intentions at McDonald’s in Jabodetabek. The method of analysis in this study uses quantitative methods using primary data obtained from distributing questionnaires as many as 130 respondents. The sampling method in this study is non probability sampling with purposive sampling technique with the testing tool used is SmartPLS. The results of this study indicate that the animosity, ethnocentrism and religiosity variable affects boycott intentions.